Social Protection for the Poor in the Developed World: The Evidence from LIS - Timothy Smeeding; Katherin E. Ross (Luxembourg Income Study (LIS), 1999)
This paper presents data and analysis on the antipoverty effectiveness of safety nets in eight rich nations using data from the Luxembourg Income Study (LIS). We find that national safety nets are quite varied and that the most expensive ones (in terms of budgetary cost) are also the most effective. The paper concludes with some suggestions for the construction of effective safety nets in developing nations.
Keywords: 330; Armutsbekämpfung; Wirkungsanalyse; Industrieländer